Data Analyzing using Big Data (Hadoop) in Billing System - Din, R; Prabadevi, B (International Journal of Computer Sciences and Engineering, 2025)
Hadoop is an open source structure in java that grants differing kind of immense datasets transversely over different groups of PCs using many programing models on which tremens -dous data works. By and large we saw that on the off chance that we increment the measure of the datasets away media, then recovering of information sets aside longer opportunity to prepare. Significant explanation behind this is because of the heap forced on information. So to take care of this kind of issues we utilize Big Data developed to fill this need. In this paper Hadoop eco-frameworks like Sqoop, hive, pig latin and so forth are utilized. Likewise we investigate expansive volume of power charging framework information and increased more prominent exactness in results, too it figures quick and furthermore recuperates loss of information.